Reconstituted HDL: Drug Delivery Platform for Overcoming Biological Barriers to Cancer Therapy - Raut, Sangram; Mooberry, Linda; Sabnis, Nirupama; Garud, Ashwini; Dossou, Akpedje Serena; Lacko, Andras (Frontiers in Pharmacology, 2018)
Drug delivery to malignant tumors is limited by several factors, including off-target toxicities and suboptimal benefits to cancer patient. Major research efforts have been directed toward developing novel technologies involving nanoparticles (NPs) to overcome these challenges. Major obstacles, however, including, opsonization, transport across cancer cell membranes, multidrug-resistant proteins, and endosomal sequestration of the therapeutic agent continue to limit the efficiency of cancer chemotherapy. Lipoprotein-based drug delivery technology, ‘nature’s drug delivery system’, while exhibits highly desirable characteristics, it still needs substantial investment from private/government stakeholders to promote its eventual advance to the bedside. Consequently, this review focuses specifically on the synthetic (reconstituted) high-density lipoprotein nanoparticles (rHDL), evaluating their potential to overcome specific biological barriers and the challenges of translation toward clinical utilization and commercialization. This highly robust drug transport system provides site-specific, tumor-selective delivery of anti-cancer agents while reducing harmful off-target effects. Utilizing rHDL nanoparticles for anti-cancer therapeutics and tumor imaging revolutionizes the future strategy for the management of a broad range of cancers and other diseases.